2005
DOI: 10.1577/ft03-220.1
|View full text |Cite
|
Sign up to set email alerts
|

Do Habitat Actions Affect Juvenile Survival? An Information‐Theoretic Approach Applied to Endangered Snake River Chinook Salmon

Abstract: We used 11 years of parr-to-smolt survival estimates from 33 Snake River sites to demonstrate that despite a number of confounding factors higher numbers of past habitat remediation or enhancement actions are associated with higher parr-to-smolt survival of endangered wild Snake River springϪsummer (stream-type) Chinook salmon Oncorhynchus tshawytscha. Information-theoretic weights were applied to help distinguish between statistical models based on their relative plausibility. In the models with the highest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Credible large-scale studies examining the effectiveness of restoration are rare (Paulsen and Fisher 2005), and many restoration projects keep poor records of construction and maintenance costs (Bernhardt et al 2005). With the lack of statistically rigorous evidence, there has been a dependence on models and expert opinion for effectiveness evaluation (Sutherland et al 2004), which makes it challenging to assess the benefits of any investment or competing recovery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Credible large-scale studies examining the effectiveness of restoration are rare (Paulsen and Fisher 2005), and many restoration projects keep poor records of construction and maintenance costs (Bernhardt et al 2005). With the lack of statistically rigorous evidence, there has been a dependence on models and expert opinion for effectiveness evaluation (Sutherland et al 2004), which makes it challenging to assess the benefits of any investment or competing recovery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses on this topic for these stocks have demonstrated that this is possible (e.g., Paulsen and Fisher 2005;Williams et al 2005). Given that most human actionswith the significant exception of marine harvest-occur in freshwater environments, their effects are at least potentially monitorable using well-established technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, they conclude that there was a "close" association between land use practices and parr-to-smolt survival. Paulsen and Fisher (2005) performed a meta-analysis on parr-tosmolt survival rate data over 11 years from 33 sites in the Snake River basin. The results indicate that areas with habitat restoration actions were associated with relatively high parr-to-smolt survival rates.…”
Section: Review Of Survival Benefits Methodsmentioning
confidence: 99%